Production of low-oxygenated bio-fuels (hydrocarbons and polymethylphenols) from lignocellulose by a two-stage strategy with non-noble metal catalysts. (15th February 2021) - Chen, Kun; Sang, Juncai; Wang, Zongxian; Ibrahim, Ummul-Khairi; Xia, Wei; Guo, Aijun; Zhang, Jia; Hou, Dan
Graphical abstract: Highlights: Low LSR yield can be obtained under low temperature and long time. Compared to N2 /H2 O/EtOH system, CO/H2 O/EtOH system improved BC yield. The addition of n-C6 H14 to methanol contributed to deep deoxygenation of BC. The alkylation and hydrogenation were paramount for producing the LOBF. The HHV of the LOBF was 40.92 MJ/kg with 7.80 wt% oxygen content. Abstract: In this work, a two-stage liquefaction-hydrogenation approach was devised to produce low-oxygenated bio-fuel from lignocellulose. At the first stage, lignocellulose was liquefied in CO/H2 O/EtOH system without catalyst at 250 °C and 12 h to produce bio-crude (BC). Around 55 wt% of bio-crude and approximately 1 wt% lignocellulose solid residue (LSR) could be obtained after liquefaction. It indicated that a low-LSR liquefaction of lignocellulose with acceptably high yield of bio-crude could be achieved under low temperature, as long as long reaction time served. It also suggested that water–gas shift reaction improved BC yield and suppressed LSR formation. At the second stage, the deoxygenation of the bio-crude was then employed in MeOH/CuZnAl-2 system at 330 °C and 6 h with the aid from n-C6 H14 and Ni/HZSM-5 to produce the low-oxygenated bio-fuel (LOBF). Notably, without coke formation, the overall yield of the LOBF reached 36.73 wt% with 7.80 wt% of oxygen content, while the HHV of the LOBF reached 40.92 MJ/kg. It was found that MeOH played a role as hydrogen donor for hydrogenation to directly decrease oxygen content and carbon source for alkylation to indirectly decrease oxygen content. Moreover, the n-C6 H14 added to methanol contributed to deep deoxygenation of bio-crude, although it had no ability of supplying hydrogen. GC × GC-TOF-MS analysis indicated that the dominant products of the LOBF were hydrocarbons and polymethylphenols. MALDI-TOF-MS analysis showed that there were no big fragments in the LOBF.